The benefit of hindsight : a Simon Serrailler case - Hill, Susan, 1942- (Hill, Susan, 1942- Simon Serrailler crime novels, 2020)
"With crime rates down, Lafferton has been quiet, until one night when a couple opens their front door to a distressing scene. Serrailler makes a serious error in judgment when handling the incident, and the stress of this, combined with the ongoing trauma of losing his arm, takes its toll. Meanwhile, Serrailler's sister, Cat, has begun a new role as a private GP, and terrible and unexpected events at the homes of two of her patients test her medical skills..."--from book jacket.